THE EFFECT OF GRAMMATICAL ACCURACY AND GENDER ON INTERLANGUAGE REQUEST STRATEGY - I Nyoman Suka Sanjaya; Anak Agung Raka Sitawati (TEFLIN Journal, 2017)
The present study was aimed at examining whether grammatical accuracy and gender were significant predictors of the use of request strategy (direct or indirect). Participants were 39 seventh semester students (29 males and 10 females) majoring in an International Business Management program at a public higher education institution in Bali. Their English proficiency levels ranged from pre-intermediate to intermediate. The participants were asked to write an e-mail based on a situation carefully designed so as to necessitate the use of indirect strategy. Grammatical accuracy was operationalized as an average score per T-unit. The head act of each request was coded as either direct or indirect, and the binary logistic regression was conducted on the data with significance level being set at p < .05. The results revealed that neither grammatical accuracy (Wald = 0.72, df = 1, p = 0.40) nor gender (Wald = 0.67, df = 1, p = 0.41) was a significant predictor of a request strategy use. The use of request strategy could not also be predicted from the interaction of grammatical accuracy and gender, Wald = 0.66, df = 1, p = 0.42. These results indicate that the odds for using indirect strategy are similar regardless of the level of grammatical accuracy and gender.